Effect of oil and gas industry in the socio-economic development of the western region of kazakhstan (The Journal of Psychology and Sociology, 2013)
Oil and gas industry has a significant impact on the socio-economic development of the country. Kazakhstan’s economic development is based on the exploitation of natural resources. One of the priorities of economic reforms in the country is the investment policy of the state, the purpose of which is the high rate of economic growth of the country which offers a positive atmosphere for foreign investments, directly in the oil and gas industry. Today, Kazakhstan is on the right path in establishing its role in the global energy sector. Thus, according to the Economic Research center, Kazakhstan ranked 16 in the world rating in terms of crude oil. The percentage the amount accounts to about 2% of the oil production in the world. Explored volume of hydrocarbon reserves is 3.3% of world reserves. Since its independence Kazakhstan has received more than 18 billion USD in direct foreign investments. Overall, there are 172 oil and 42 gas fields located in the territory of Kazakhstan and 80 fields are in development. Oil and gas areas cover about 62% of the total territory of Kazakhstan. About 90% of oil reserves in Kazakhstan are concentrated in 15 major fields - Tengiz, Kashagan, Karachaganak, Uzen Zhetybai, Zhanazhol Kalamkas Kenkiyak, Karazhanbas Kumkol North Buzachi, Alibekmola, Prorva CEE, Kenbai, Royal.Fields are located in six of the fourteen regions of Kazakhstan: Aktobe, Atyrau, West Kazakhstan, Karaganda, Kyzylorda and Mangistau. Where, about 70% of the hydrocarbons are concentrated in western Kazakhstan.The paper pays particular attention to the impact of oil and gas industry on the social development of the regions of western Kazakhstan, just change the standard of living of the population. So examples of the positive impact and the negative impacts are provided. Also, the changes occurring in the region with the arrival of foreign companies have been analyzed. Has the situation improved for the local workforce, is the level of knowledge of the local staff enough to be employed by the foreign companie. The largest oil companies in the region are TCO, RD «KazMunaiGas» and Karachaganak Petroleum Operating. The share of these companies accounts for over 60% of the total oil production in the country. As expected from the large companies, social policy in these enterprises is an important trend of their activity. Employment is important sector of the economy, so the companies take up a heavy responsibility for the social and economic situation in the region.
Keywords: oil and gas industry; oil and gas fields; socio-economic development; foreign companies.